Description of Patient Satisfaction Towards Dental and Oral Health Services During Bulan Kesehatan Gigi Nasional (BKGN) 2022 At The Dentistry Study Program of Mulawarman University - Septimaulida, Firda; Adrianto, Ratno; Nurrachmawati, Annisa (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Patient satisfaction is the primary indicator of the standards of a healthcare facility and a measure of service quality. When patient expectations are met by high-quality healthcare services, it results in a high level of service quality. There are several factors that affect oral health, including genetics, environment, behavior, and services. Riskesdas (2018) reported that 61.5% of the population in East Kalimantan faced oral health issues, with only 13.8% seeking treatment from dental professionals. In response, the Dentistry Study Program at Mulawarman University organized free dental care services during BKGN 2022, aiming to promote oral health awareness. This threeday event, held from December 5 to 7, 2022, included oral health counseling, tooth extraction, tooth filling, tartar cleaning (scaling), topical fluoride application, and fissure sealant procedures. Objective : The aim of this study was to explore an overview of patient satisfaction with dental and oral health services in Bulan Kesehatan Gigi Nasional (BKGN) 2022. Research Methods/ Implementation Methods : This study was a quantitative descriptive study with cross-sectional research design with a sample size of 300 individuals (total sampling). In this study, patients who have completed their treatment were asked to fill out a quetionnaire. Results : Descriptive analysis of the data revealed that tartar cleaning (scaling) was the most frequently performed procedure, accounting for 41% of cases. In terms of gender, women (66%) sought dental care more frequently than men (34%). Regarding age groups, the highest frequency of oral care was observed among individuals aged 17-25 years, corresponding to the late adolescence stage. Overall, the distribution of respondents who stated that they were satisfied with the oral health services at BKGN 2022 was (55.3%) and patients who stated that they were very satisfied were (36%). Conclusion/Lesson Learned : Overall, the distribution of respondents who stated that they were satisfied with the oral health services at BKGN 2022 was (55.3%). The predominant type of oral care provided during BKGN 2022 was scaling, whereas fissure sealants were the least commonly administered treatment.